Positive Mental Wellbeing: A Validation of a Rasch-Derived Version of the Warwick-Edinburgh Mental Well-Being Scale - Houghton, S.; Wood, L.; Marais, I.; Rosenberg, M.; Ferguson, R.; Pettigrew, Simone (SAGE Publications, 2016)
This study presents a Rasch-derived short form of the Warwick-Edinburgh Mental Well-Being Scale for use as a screening tool in the general population. Data from 2,005 18- to 69-year-olds revealed problematic discrimination at specific thresholds. Estimation of model fit also deviated from Rasch model expectations. Following deletion of 4 items, the 10 remaining items indicated the data fitted the model. No items showed differential item functioning, thereby making comparisons of overall positive mental well-being for the different age, gender, and income groups valid and accurate. Cronbach’s alpha and Rasch Person Separation Index indicated a strong degree of reliability. Overall, the 10-item scale challenges researchers and clinicians to reconsider the assessment of positive mental well-being.